PERSONAL DATA SECURITY FOR SMART SYSTEMS AND DEVISES WITH REMOTE ACCESS - P. Veleva (Trakia Journal of Sciences)
Issues related to the personal data security of users of smart devices with remote access are discussed in the paper. An empirical study through a structured interview and a web-based survey via e-mail and social media conducted by a specific company is presented. The actions taken by the company to ensure the security and personal data protection of its users and business partners are presented. The company's main activity is designing and constructing automatic systems and electronic devices with remote access via the Internet. The survey is part of the company's activity to achieve good business results, loyal and accurate corporate policy benefitting all contracting partners and long-term business partnerships.